Atomização do jato líquido em um lavador venturi - Puentes, Néstor Alejandro Gómez (Universidade Federal de São Carlos, 2008)
Pease-Anthony Venturi gas scrubbers are well known equipments used when collection efficiency demands are superior to 90%. It utilizes liquid, in the form of droplets, to collect the pollutants. Initially, the droplets are concentrated in areas near the trajectory of jets from injection of liquid. The droplets are dispersed throughout the equipment, by reason of turbulence. Some of the main phenomena that affect the collection efficiency of a Pease-Anthony Venturi scrubber, as the penetration and trajectory of the liquid jet (distance covered for the liquid jet until its atomization) and the angle of spreading formed inside the throat are presented. With the purpose of obtaining a better understanding of the variables mentioned above, photographic images of the process of atomization of a liquid jet into the throat of a Pease-Anthony Venturi scrubber were taken, with throat gas velocities between 59 and 74m/s, jet velocities between 3.18 and 19.10m/s and liquid injected into the throat through different orifices.
Keywords: Atomização; Lavador venturi; Jato - penetração; Jato - trajetória; Imagens fotográficas; ENGENHARIAS::ENGENHARIA QUIMICA